2009
DOI: 10.1016/j.cell.2009.07.047
|View full text |Cite|
|
Sign up to set email alerts
|

Norrin, Frizzled-4, and Lrp5 Signaling in Endothelial Cells Controls a Genetic Program for Retinal Vascularization

Abstract: SUMMARY Disorders of vascular structure and function play a central role in a wide variety of CNS diseases. Mutations in the Frizzled4 (Fz4) receptor, Lrp5 co-receptor, or Norrin ligand cause retinal hypovascularization, but the role of Norrin/Fz4/Lrp signaling in vascular development has not been defined. Using mouse genetic and cell culture models, we show that loss of Fz4 signaling in endothelial cells causes defective vascular growth, which leads to chronic but reversible silencing of retinal neurons. Loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
428
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(457 citation statements)
references
References 45 publications
24
428
3
2
Order By: Relevance
“…All of these genes are potent proangiogenic genes associated with ocular angiogenesis. FZD4 is a receptor for Wnt signaling, which is a highly conserved angiogenic pathway activated in both OIR and laser-induced CNV models (16,33,34). On the other hand, Dll4/Notch signaling controls vessel sprouting and branching, and inhibition of DLL4 showed reduced pathological neovessels in OIR (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these genes are potent proangiogenic genes associated with ocular angiogenesis. FZD4 is a receptor for Wnt signaling, which is a highly conserved angiogenic pathway activated in both OIR and laser-induced CNV models (16,33,34). On the other hand, Dll4/Notch signaling controls vessel sprouting and branching, and inhibition of DLL4 showed reduced pathological neovessels in OIR (35).…”
Section: Discussionmentioning
confidence: 99%
“…To identify potential target genes of miR-150, we analyzed the seed sequence of miR-150 (CUCCCAA), conserved in both human and murine for complementarity with predicted target mRNAs. Three candidates were identified, which are associated with angiogenesis and retinopathy (15)(16)(17): CXCR4, DLL4, and FZD4. All contained potential miR-150 seed targeting sequences in their 3′ UTRs (Fig.…”
Section: Vascular-enriched Mir-150 Was Significantly Suppressed In Pamentioning
confidence: 99%
“…Interestingly, several recent studies also support a role for VEGF-independent signaling by Müller cells in developmental angiogenesis. For example, Müller cells secrete Norrin, a retinal signaling molecule which binds to Frizzled-4 to activate canonical Wnt/-catenin signaling, in the absence of which the development of the superficial vessels was attenuated and deeper intraretinal capillaries were not formed Ye et al, 2009;Ohlmann and Tamm, 2012). Also, the deletion of hypoxia inducible factor-1 in neuroretinal cells (includes Müller cells) results in impaired vascular development characterized by decreased tip cell filopodia and reduced vessel branching (Nakamura-Ishizu et al, 2012), a phenotype very similar to that of sEH / mice.…”
Section: Discussionmentioning
confidence: 99%
“…The Pdgfrb‐Cre line (Foo et al ., 2006), where Cre recombinase expression is driven by a transgenic fragment of the gene for platelet‐derived growth factor receptor β ( Pdgfrb ), has been used extensively to specifically target mural cells, namely vascular smooth muscle cells, pericytes and hepatic stellate cells; examples are given in ref (Abraham et al ., 2008; Foo et al ., 2006; Greif et al ., 2012; Henderson et al ., 2013; Jeansson et al ., 2011; Kogata et al ., 2009; Siegenthaler et al ., 2013; Stenzel et al ., 2009; Ye et al ., 2009; You et al ., 2014). We (Stanczuk et al ., 2015) and others (Klotz et al ., 2015) recently showed that Pdgfrb‐Cre unexpectedly also targets a large proportion of embryonic lymphatic endothelial cells (LECs) in the developing mesentery (Stanczuk et al ., 2015) and the heart (Klotz et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%